The Mekong delta water resources project = (The World Bank in Vietnam (WB), 2003)
The Mekong Delta Water Resources Project aims at improving the water resources infrastructure in five subproject areas, divided by hydrological boundaries. The prevention of salinity intrusion on canals serving the agricultural areas, and the improvement of existing irrigation systems, for those subprojects located in the lower delta, are the main objectives. The main issues concerning the Omon-Xano subproject, located in the mid-delta, are to improve flood protection and drainage. The project will facilitate local water and land transport, and will finance land acquisition, compensation, and resettlement expenses, incurred in as a consequence of the project. The project's main components will: 1) improve water resources infrastructure, through construction of primary, secondary, and tertiary canals, together with the necessary embankments, bridges, and roads. Compensation for land acquisition and resettlement will be provided, as well as training to affected families in drainage management systems; 2) improve rural water supply and sanitation, through clean water provision and better sanitation processes; 3) strengthen water resources management and improve environmental monitoring through institutional capacity building. The component will manage engineering design, implementation and supervision, and provide institutional technical assistance and training.